Proses Pengasuhan Anak Balita pada Ibu Pekerja - Fitriana, Indah Widya; Husin, Azizah; Tahyudin, Didi (Journal of Nonformal Education and Community Empowerment, 2019)
This study aims to describe the process of caring for children under five in working mothers from the aspect of care and aspects of the role of mothers in the village of Pedamaran V, Ogan Komering Ilir district. This type of research is descriptive using a qualitative approach. The subjects of this study are mothers who work more than 8 hours per day with work as fishermen, laborers, and traders and also 3 people who help in the process of caring for children under five. The results of this study the role of mothers goes well because there are other people who help mothers both from the aspect of care and aspects of the role of the mother is the process of caring for children under five in working mothers has been done well.